Microstructure-Mechanical Properties and Application of Magnesium Alloys - Al-Samman, Talal; Yi, Sangbong; Letzig, Dietmar (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue reprint book features a broad scope of contributions that highlight current accomplishments and provide readers with some perspective on the direction of research on magnesium alloys in the near future with respect to global challenges. The papers included in the book report on state-of-the-art methods and research trends regarding the microstructure, properties and industrial application of magnesium alloys for use in lightweight structures across several industries.